2018
DOI: 10.7598/cst2018.1513
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition and Antibacterial Activity of Agrimonia Pilosa Ledeb (Rosaceae)

Abstract: Essential oil composition of the aerial parts of Agrimonia pilosa Ledeb growing wild in the central Himalayan region of Uttarakhand, India was analyzed by capillary gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS). A total of 15 constituents were identified, representing 95.29% of the oil composition. The oil consisted mainly of oxygenated monoterpenes (75.74%) followed by monoterpene hydrocarbons (18.68%). Major constituents identified were methyl myrtenate (71.39%), limonene (11.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…An accumulating quantity of research has demonstrated that many plants used in traditional Chinese medicine have antibacterial activity both in vitro and in vivo in poultry production [15]. More specifically, the antibacterial properties of solvent extracts of Agrimonia pilosa Ledeb, Smilax glabra Roxb, Anemone chinensis Bunge, and Iris domestica (L.) Goldblatt and Mabb have been documented through in vitro screening [16][17][18][19]. Aqueous extraction methods are inexpensive and the bioactive compounds are less toxic and therefore more suitable for use as a poultry feed supplement.…”
Section: Introductionmentioning
confidence: 99%
“…An accumulating quantity of research has demonstrated that many plants used in traditional Chinese medicine have antibacterial activity both in vitro and in vivo in poultry production [15]. More specifically, the antibacterial properties of solvent extracts of Agrimonia pilosa Ledeb, Smilax glabra Roxb, Anemone chinensis Bunge, and Iris domestica (L.) Goldblatt and Mabb have been documented through in vitro screening [16][17][18][19]. Aqueous extraction methods are inexpensive and the bioactive compounds are less toxic and therefore more suitable for use as a poultry feed supplement.…”
Section: Introductionmentioning
confidence: 99%